THE IMPACTS OF DICTION MASTERY AND RHETORICAL TECHNIQUES ON STUDENTS' SPEECH WRITING: A CASE STUDY AT SMK NEGERI 3 LHOKSEUMAWE - Sitti Aminah; Ainol Mardhiah; Meri Hari Yanni (RADJA PUBLIKA, 2023)
This study explores the challenges faced by high school students at SMK Negeri 3 Lhokseumawe in using diction and rhetorical techniques in speech writing. Despite the significance of these skills for persuasive communication, many students encountered difficulties. A qualitative case study was conducted with 10 students from grade X, employing semi-structured interviews, classroom observations, and document analysis. The study identified five challenges: limited vocabulary, difficulty applying rhetorical techniques, lack of exposure to effective speech samples, fear of experimenting with advanced language, and insufficient feedback on language use. The findings emphasize the need for targeted instructional strategies, including vocabulary-building activities, explicit teaching of rhetorical techniques, and more personalized feedback. This research underscore the importance of enhancing diction and rhetorical skills in vocational schools, where the focus is often on functional communication rather than expressive language use. The study offers valuable insights for teachers seeking to improve speech writing instruction in vocational contexts, providing a foundation for future pedagogical interventions aimed at addressing these challenges and fostering more effective communication skills among students.